Evaluation of pedagogical directive leadership and teaching performance in the area of history, geography and economics. Case: third, fourth and fifth year high school students from the parochial educational institution "Our Lady of the Rosary" - Carhuavilca Quispe, Ynes Aurora (2020)
One of the key problems in the teaching of students of Regular Basic Education, is the perplexity and high level of mistrust that exists between teachers and their directive authorities especially in the pedagogical. In this research it was demonstrated that the Pedagogical Management Leadership Evaluation is related to the Pedagogical Competencies of the secondary level teacher in the Parish Educational Institution "Our Lady of the Rosary". Independence. UGEL N ° 02. Lima 2018., since it is through a p whose value less than 0.05 in the statistical analysis, this relationship is shown with a correlation coefficient, r = 0, 768 which represents a correlation of 76.8%. And it is related through the personal competences of the Teacher whose correlation coefficient, r = 0,593, which represents a correlation of 59,3%. The competences from the institutional management have a r = 0, 543 which represents a correlation of 54.3%. The skills of communicative management have a significant relationship whose r = 0, 638 which represents a correlation of 63.8%. It is important to take these correlations into account in order to reduce this gap between weak pedagogical management leadership and the competencies that the teacher should develop.